3D CFD study of hydrodynamics and mass transfer phenomena for spiral wound membrane submerged-type feed spacer with different node geometries and sizes. (1st August 2022) - Chong, Y.K.; Liang, Y.Y.; Lau, W.J.; Fimbres Weihs, G.A.
Highlights: Submerged type spacers with different node geometry and size are evaluated. Column nodes divert more flow to the filaments than spherical nodes. Larger column diameter leads to larger vortices which cause more mixing. Column nodes spacer is more promising for high feed rate flow RO systems. Smaller channel height may improve mass transfer using submerged spacer. Abstract: Modification of the spacer geometry is a promising approach to increase the efficiency of reverse osmosis (RO) spiral wound membrane modules. Column nodes and spherical nodes are considered in this three-dimensional computational fluid dynamic (CFD) study to evaluate the hydrodynamic and mass transfer performance of submerged spacers with different node geometries and sizes. Small-scale CFD analysis results reveal that the column node has better mass transfer performance than the spherical node geometry because column nodes divert more flow to the filaments, leading to higher local velocity at the region between the filament and wall. Furthermore, when the dimensionless node diameter ratio of the column nodes increases from 0.3 to 1.2, Sherwood number and wall shear increase by 25% and 8% respectively at the expense of higher global friction factor (44%). A sea water RO full-scale analysis revealed that column node spacers yield higher average flux than spherical nodes and conventional spacers at high feed inlet velocity (> 0.1 m/s), because the mixing effects by the spacer that improve mass transfer are more prominent.